The Effect of Service Quality Perception and Price Perception on Customer Loyalty of the Gojek Application Mediated by Satisfaction - Retno Widowati; Naufal Athalla (International Publisher (YAPENBI), 2025)
The purpose of this study is to test and analyze the influence of Perception of Service Quality and Perception of Price on Customer Loyalty of the Gojek application mediated by Customer Satisfaction. The data used in this study are primary data using a questionnaire, the measurement scale used is a Likert scale of 1-5. The sampling technique used in this study used purposive sampling and obtained research data of 225 samples. The method used in this study is SEM Amos. The results of data analysis and hypothesis testing indicate that Perception of Service Quality has no effect on Customer Satisfaction. Perception of Price has a positive and significant effect on Customer Satisfaction. Perception of Service Quality has a positive and significant effect on Customer Loyalty. Perception of Price has a positive and significant effect on Customer Loyalty. Customer Satisfaction has no effect on Customer Loyalty. Customer Satisfaction is unable to mediate Perception of Service Quality on Customer Loyalty. Customer Satisfaction is unable to mediate Perception of Service Price on Customer Loyalty. Providing information or reading materials to advance understanding in the field of marketing management, especially related to Perception of Service Quality and Perception of Price towards customer loyalty mediated by customer satisfaction. The object used in this study is the Gojek application, with the research subjects being Gojek application users among students of Muhammadiyah University of Yogyakarta.